PENGARUH PUPUK ORGANIK CAIR PADA POLA KUNJUNGAN SERANGGA DI PERKEBUNAN APEL (Malussylvestris Mill.) PASCA ERUPSIGUNUNG KELUD - Habibi Indra Muhammad; Amin Setyo Leksono; Nia Kurniawan; Bagyo Yanuwiadi (Universitas Tribhuwana Tunggadewi, 2016)
Negative impacts of dust-mount volcanic eruption to the production and damages of the surrounding plantation have been understood. However, its environmentally friendly mitigation effort has been poorly investigated. Application of organic fertilizer has been reported to be able to recover crop’s ecosystem balance, especially through insect’s community balance. Study on the effect of organic fertilizer application on insect visitation pattern at apple plantation following dust volcanic eruption of Mount Kelud was assessed at Junggo village, Malang regency, from January to April 2015. Treatments consisted of liquid organic fertilizer (LOF) at the rate of 2 cc/lt applied at blooming and fruiting seasons (LOF flower and LOF fruit) and controls. Sample size was 6plants. Liquid orgamicfertilizer were applied 10 times; five times during flowering time and the remaining five at fruiting time. Observation was made four days after application at 4 period intervals, namely, 0.7.00-08.00; 09.00-10.00; 12.00-13.00 and 15.00-16.00. Parametersobserved include insect diversity, abundance,and composition. Results showed that application of Liquid Organic Fertilizer (LOF) significantly affected the insect visitation pattern. LOF at flowering time showed the highest diversity index. Insect diversity consisted of 14 families. The highest composition shown by the pollinator and among the pollinators, the Tabanidae was the most importance. These finding signify that Liquid Organic Fertilizer (LOF) has been proven as one of the potential mitigation effort that environmentally friendly